Que sais-je? qui suis-je? Autoportraits et écriture intime au XVIIIe siècle - Seth, C (Classiques Garnier, 2018)
In their life-writing, Enlightenment women (un)consciously depict themselves. This article examines different attitudes on the basis of texts by Mary Robinson, Victoire Monnard, Adélaïde de Castellane, Françoise-Radegonde Le Noir, Jeanne-Marie Roland, Suzanne Necker and Charlotte-Nicole Coquebert de Montbret, as well as of painted self-portraits by Rosalba Carriera and Élisabeth Vigée-Lebrun.